Ongoing and planned activities to improve the management of patients with Type 1 diabetes across Africa; implications for the future. Issue 2 (14th March 2020) - Godman, Brian; Basu, Debashis; Pillay, Yogan; Almeida, Paulo H. R. F.; Mwita, Julius C.; Rwegerera, Godfrey Mutashambara; Anand Paramadhas, Bene D; Tiroyakgosi, Celda; Patrick, Okwen; Niba, Loveline Lum; Sefah, Israel; Oluka, Margaret; et al.
ABSTRACT: Background: Currently about 19 million people in Africa are known to be living with diabetes, mainly Type 2 diabetes (T2DM) (95%), estimated to grow to 47 million people by 2045. However, there are concerns with early diagnosis of patients with Type 1 diabetes (T1DM) as often patients present late with complications. There are also challenges with access and affordability of insulin, monitoring equipment and test strips with typically high patient co-payments, which can be catastrophic for families. These challenges negatively impact on the quality of care of patients with T1DM increasing morbidity and mortality. There are also issues of patient education and psychosocial support adversely affecting patients' quality of life. These challenges need to be debated and potential future activities discussed to improve the future care of patients with T1DM across Africa. Methodology: Documentation of the current situation across Africa for patients with T1DM including the epidemiology, economics, and available treatments within public healthcare systems as well as ongoing activities to improve their future care. Subsequently, provide guidance to all key stakeholder groups going forward utilizing input from senior-level government, academic and other professionals from across Africa. Results: Whilst prevalence rates for T1DM are considerably lower than T2DM, there are concerns with late diagnosis as well as the routine provision of insulin and monitoring equipment across Africa. High patient co-payments exacerbate the situation. However, there are ongoing developments to address the multiple challenges including the instigation of universal health care and partnerships with non-governmental organizations, patient organizations, and pharmaceutical companies. Their impact though remains to be seen. In the meantime, a range of activities has been documented for all key stakeholder groups to improve future care. Conclusion: There are concerns with the management of patients with T1DM across Africa. A number of activities has been suggested to address this and will be monitored.